Trans-abdominal cervical cerclage revisited - Svigos, John (Clinical Journal of Obstetrics and Gynecology, 2019)
Changes in contemporary obstetric and gynaecological practice in relation to ultrasound cervical screening during pregnancy, the treatment of intra-epithelial cervical neoplasia and laparoscopic surgery have resulted in an increased utilization of trans-abdominal cervico-isthmic cerclage in an attempt to reduce the incidence of mid-trimester and early preterm birth in women with repeated pregnancy loss.